Involvement of pannier and u-shaped in regulation of Decapentaplegic-dependent wingless expression in developing Drosophila notum. - Sato, M.; Saigo, K. (Mechanisms of Development, 2000)
In developing Drosophila notum, wingless expression is regulated by Decapentaplegic signaling positively and negatively so that only notal cells receiving optimal levels of Decapentaplegic signals express wingless (Sato et al., 1999b. Development 126, 1457-1466). Here, we show evidence that this Decapentaplegic-dependent regulation of notal wingless expression includes plural mechanisms, involving pannier and u-shaped. In the medial notum, Pannier and U-shaped form a complex (Haenlin et al., 1997. Genes Dev. 11, 3096-3108). The expression of pannier and u-shaped is positively regulated by Decapentaplegic signals emanating from the dorsal-most region. The Pannier/U-shaped complex serves as a repressor and a transcriptional activator, respectively, for wingless and u-shaped expression. In the more lateral region, wingless expression is up-regulated by U-shaped-unbound Pannier. wingless expression is also weakly regulated by its own signaling.